Participative Budgeting: Effects of a Truth-Inducing Pay Scheme and Information Asymmetry on Slack and Performance - Chow, Chee W.; Cooper, Jean C.; Waller, William S. (The Accounting Review, 1988)
[This paper provides empirical evidence on a truth-inducing pay scheme widely discussed and analyzed in the incentive contracting literature. An experiment was conducted in which subjects acted as subordinates who performed a production task. Budgets were participatively set under either a truth-inducing or slack-inducing pay scheme and either the presence or absence of a superior-subordinate information asymmetry about subordinate performance capability. Slack was defined as expected performance minus the participatively set budget. The results showed that, when the information asymmetry was absent, slack did not differ significantly between the pay schemes. However, when the information asymmetry was present, slack was significantly lower under the truth-inducing scheme. Similarly, the pay scheme and information asymmetry variables interacted to affect performance.]